THE INFLUENCE OF THE DEMONSTRATION METHOD ON THE LEARNING MOTIVATION OF CLASS VI STUDENTS OFSDN 078553 ORLIN, SOUTH NIAS REGENCY ONINDONESIAN LANGUAGE SUBJECTS - Diana Siska Laka; Ulil Azmi (Journal of Learning on History and Social Sciences, 2024)
The demonstration method is very important in teaching because it makes abstract concepts more concrete and easier for students to understand. In addition, demonstrations involve students directly in the learning process. They can see, hear, and often participate in demonstrations, which helps improve information retention. Meanwhile, motivating students is one of the most important aspects of effective teaching. This research aims to determine the effect of the demonstration method on the learning motivation of class VI students at SDN 078553 Orlin in Indonesian language subjects. The method used in this research is a qualitative descriptive method. The sample in the research was class VI, 32 people. Data collection techniques are interviews, observation and documentation. The results of the research conducted provide information that the demonstration method is very efficient in helping to shape students' characters such as cooperation, responsibility, caring, tolerance and is able to increase students' learning motivation. The demonstration method is never separated from the teacher's control to monitor the development of learning outcomes so that it can have a positive influence.